Comparison of Unstimulated Salivary Flow Rate and Salivary pH Before, Immediately After, and 40 Minutes Following Consumption of Arabica and Robusta Coffee in Women - Nabillah Hidayah Sari; Ahmad Ronal; Audiawati Surachmin (Journal of Indonesian Dental Association, 2026)
Introduction: Saliva is an important exocrine secretion in the oral cavity that plays a role in lubrication, mechanical cleansing, antimicrobial activity, and pH buffering. Coffee consumption can affect saliva characteristics due to its acidic nature and caffeine content. Arabica coffee contains lower caffeine (0.8–1.4%) with a smoother taste, while Robusta has higher caffeine (1.7–4.0%). Objective: To determine the comparison of unstimulated salivary flow rate and pH before, immediately after, and 40 minutes after consuming Arabica and Robusta coffee. Methods: Comparative analytic quasi-experimental design with 20 female participants aged 18–22 years per group, selected via purposive sampling, healthy without systemic disorders, medications affecting saliva, orthodontic treatment, active caries, or mildly underweight to mildly overweight BMI. Extracting 60 grams of coffee using a coffee machine to produce 150 mL solution without sediment. Sequential treatments: Day-1 plain water, Day-2 Arabica, Day-3 Robusta; measurement of salivary flow rate and pH using spitting. Data analysis using Friedman and Wilcoxon tests. Results: Before intervention, no significant differences were observed in salivary flow rate (p > 0.841) or salivary pH (p > 0.137). Both Arabica and Robusta coffee solutions significantly increased salivary flow rate immediately after consumption (p < 0.008). At 40 minutes, salivary flow rate remained significantly higher in the Arabica group compared with Robusta (p = 0.029). Conclusion: Coffee consumption significantly increased unstimulated salivary flow rate, the Arabica more sustained stimulatory effect than Robusta. Although transient pH fluctuations occurred after coffee consumption, salivary pH did not differ significantly between interventions.